Optimizing Student Organizational Sustainability: Integrating Psychological Training into Leadership Development - Misbahul Arifin (Al-Qalam Institute, 2026)
Organizational communication is essential for maintaining effective collaboration and collective decision-making within student organizations. This study aims to examine the role of Solution-Focused Training and its psychological impact on organizational communication within a student organization. The research employed a qualitative case study approach involving organizational members as participants, with data collected through in-depth interviews, participant observation, and document analysis. Thematic analysis was used to identify patterns of communication change following the training intervention. The findings reveal three main outcomes: communication patterns became more structured and solution-oriented during meetings, member participation in discussions increased significantly, and members demonstrated stronger psychological readiness reflected in higher motivation, confidence, and resilience. These results indicate that the training not only improved communication techniques but also strengthened the psychological conditions that support effective interaction. The study contributes by extending the application of solution-focused approaches to value-based student organizations and recommends integrating psychological training into leadership development programs to enhance the sustainability of organizational communication.